Perlindungan Kawasan Hutan Negara atas Kegiatan Pemungutan Hasil Hutan Tanpa Izin: Studi Putusan Nomor 40/PID.SUS/2019/PN.PKY (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2026)
This research aims to analyze the protection of state forest areas against unauthorized forest product collection in Pasangkayu Regency, specifically from the perspective of preventive and repressive legal protection. The research method used is normative juridical with a descriptive-analytical nature, utilizing secondary data collected through literature studies. The results indicate that forest area protection in Pasangkayu Regency is currently still dominated by a repressive approach, namely legal actions taken after violations occur, such as enforcement operations and criminal proceedings. However, this approach has proven ineffective in providing a maximum deterrent effect due to the high rate of violations triggered by low legal awareness and the community's economic dependence on forest products. Meanwhile, preventive efforts such as monitoring and legal counseling have not operated optimally due to limitations in human resources and budget. Therefore, a balance between preventive and repressive approaches is required, along with strengthening community participation through economic empowerment to enhance the effectiveness of forest protection.